Estimation of Passenger Demand in Urban Public Transport - Horváth, B.; Horváth, R.; Gaál, B. (Acta Technica Jaurinensis, 2013)
This article shows a renewed, improved, practical variant of a former theoretical matrix estimation method. The authors will demonstrate the method’s theoretical and practical sides on a test network.